Studi Klasifikasi Jenis Tanah Dan Analisis Kecepatan Gelombang Geser Menggunakan Metode Inversi HVSR Di Kota Serang, Banten - Sandy Tri Gustono; Muhammad Bintang Nugroho; Bambang Sunardi; Khairina Fauzi (Universitas Islam Negeri Alauddin Makassar, 2023)
Serang City is a city that is prone to earthquakes. To minimize the disaster impact, the identification of dynamic and local soil conditions is needed. One of the methods that can be used is microtremor. Microtremor measurements have been carried out by the BMKG’s Seismotek Team in all areas of Serang City. Furthermore, the microtremor data was processed using the Horizontal to Vertical Spectral Ratio (HVSR) method to analyze the predominant frequency curve and value. Then the inversion method is applied to the results to obtain the model of the shear wave velocity (Vs) values. The results of modeling are then used to calculate the distribution of Vs30 values and classification of soil types and also modeled in 3-D to identify sediment thickness in Serang City. Microtremor data processing shows that the predominant frequency values in Serang City vary. The predominant frequency value ranges from 0,57 to 14,27 Hz. Then the results of the HVSR inversion obtained Vs30 in Serang City around 190 – 1400 m/s. Based on the soil classification by SNI 1726:2019, the type of soil varies from soft soil (SE), medium soil (SD), hard soil, and soft rock (SC), and there is one 1 data with rock soil classification (SB). The value of the Vs tends to be low in the north and east areas and increases further in the south and west area.